Red Blood Cell Distribution Width and Neutrophil-to-Lymphocyte Ratio in Predicting Adverse Outcomes of Acute Kidney Injury in Hospitalized Patients - Jiefu Zhu; Cong Zeng; Lei Zhang; Shaoqun Shu; Yinghong Liu; Guochun Chen; Hong Liu; Yu Liu; Zheng Dong (Karger Publishers, 2020)
Background: Acute kidney injury (AKI) is a common clinical condition with high morbidity and mortality. Early risk stratification by identifying patients at risk for death or dialysis requirement has important therapeutic implications for timely interventions. Objective: The aim of this study was to examine the association of routine blood test parameters, specifically red blood cell distribution width (RDW) and neutrophil-to-lymphocyte ratio (NLR), with the AKI patient outcomes. Methods: All adult patients hospitalized from January 1, 2016, to June 30, 2016, in the Second Xiangya Hospital of Central South University were surveyed. Demographic characteristics, laboratory measurements, comorbidities, and outcomes of a total of 1,188 adult AKI patients were analyzed. Results: The incidence of AKI was 1.8% (1,188/65,329). The all-cause mortality was 16.0% (190/1,188). The multivariable relative risk of AKI mortality comparing high RDW with low RDW was 1.84 and the risk comparing high NLR with low NLR was 2.54. RDW and NLR combination showed additive values in stratifying high-risk patients, and the predictive power was comparable to the use of serum creatinine for staging AKI. In subgroup analyses, high RDW predicted prerenal AKI mortality better than intrinsic AKI. High RDW and NLR also independently predicted renal replacement therapy (RRT) requirement in AKI patients. In contrast, WBC count and platelet-to-lymphocyte ratio did not show obvious correlations with death and RRT requirement in AKI patients. Conclusion: The results support the potential usefulness of RDW and NLR in risk stratification of AKI patients, providing additional prognostic information for treatment and supportive care.